2014
DOI: 10.1186/2193-1801-3-667
|View full text |Cite
|
Sign up to set email alerts
|

Single-breath-hold whole-heart coronary MRA in healthy volunteers at 3.0-T MRI

Abstract: BackgroundThe purpose of this study was to investigate the feasibility of single-breath-hold whole-heart MRA with a 3-T system. Ten healthy male volunteers underwent single-breath-hold whole-heart coronary MRA at 3 T. We assessed acquisition time, scores of image quality of coronary artery (RCA: proximal, middle and distal, LAD: main, proximal, middle and distal, LCX: proximal and distal) and the visualized vessel length of RCA, LAD and LCX.FindingsMean acquisition time was 37.7 ± 5.2 sec. Coronary branch was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Recent 3T MRI system using TFE sequence can offer adequate SNR in spite of having the short acquisition time of whole-heart coronary MRA because the SNR is proportional to the static field strength. 5 However, the spatial resolution of single breath hold unenhanced coronary MRA with TFE was relatively low 5 (Spatial resolution; 2.00 × 2.00 × 2.00). Additionally, the single breath hold unenhanced coronary MRA with TFE required relatively long time (37.7 ± 5.2 sec, 31 sec to 45 sec).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent 3T MRI system using TFE sequence can offer adequate SNR in spite of having the short acquisition time of whole-heart coronary MRA because the SNR is proportional to the static field strength. 5 However, the spatial resolution of single breath hold unenhanced coronary MRA with TFE was relatively low 5 (Spatial resolution; 2.00 × 2.00 × 2.00). Additionally, the single breath hold unenhanced coronary MRA with TFE required relatively long time (37.7 ± 5.2 sec, 31 sec to 45 sec).…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 In addition, previous report suggested the usefulness of single breath hold unenhanced coronary MRA with turbo field echo (TFE) technique. 5 They reported that the single-breath hold technique can shorten the total scan time and reduce the influence of respiratory motion. On the other hand, this sequence suffers from sensitivity to B0 inhomogeneity at 3T MRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Ultimately even one-breath-hold scanning has recently been reported combining these advanced technologies. 9 However, these hardware and software are not always available and the one-breath-hold imaging is obtained at the expense of spatial resolution. Explanation and practice of stable respiration are important but not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…While Compressed Sensing enables higher acceleration than conventional Parallel Imaging, acquiring sufficient data with the required level of image quality in one breath-hold is a challenging task. In [18] a single breath-hold acquisition protocol for imaging of the coronary arteries was presented. The average acquisition time in their approach was 37.7 ± 5.2 s which reveals potential for improvement.…”
Section: Acquisition Protocolmentioning
confidence: 99%